. If p(x)= x³+ 3x²- 2x +4, then
find the value of p(2) + p(-2) – p(0)​

Question

. If p(x)= x³+ 3x²- 2x +4, then
find the value of p(2) + p(-2) – p(0)​

in progress 0
Mackenzie 4 months 2021-07-18T23:22:54+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-18T23:24:25+00:00

    {Solution}

    Given:-

    p(x) = x³ + 3x² – 2x + 4

    To find :-

    Value of p(2) + p(-2) -p(0)

    SOLUTION:-

    First Lets find p(2) that means we have to substitute x = 2

    p(2) = x³ + 3x² – 2x + 4

    p(2) = (2)³ +3(2)² -2(2) + 4

    p(2) = 8 + 3(4) -4 + 4

    p(2) = 8 + 12 – 4 + 4

    p(2) = 20

    Now for finding p(-2) that means we have to substitute x= -2

    p(-2) = x³ + 3x² -2x + 4

    p(-2) = (-2)³ +3(-2)² -2(-2)+4

    p(-2) = -8 + 3(4) +4 +4

    p(-2) = -8 + 12 + 8

    p(-2) = 12

    Now for finding p(0) that means we have to substitute x=0

    p(0) = x³ + 3x² -2x + 4

    p(0) = (0)³ + 3(0)² -2(0) + 4

    p(0) = 0+0 +0 +4

    p(0) = 4

    Now we need p(2) + p(-2) + p(0)

    = 20 + 12 + 4

    = 36

    So, the value of p(2) + p(-2) – p(0) is 36

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )